Water yield and consumption of cauliflower plants grown in a hydroponic system using brackish waters and different flow rates - Ruana I. F. Cruz; Gerônimo F. da Silva; Ênio F. de F. e Silva; Hammady R. e Soares; José A. Santos Júnior; Hugo R. B. Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
HIGHLIGHTS Raising the flow rate of the nutrient solution with brackish water results in less water consumption in cauliflower. The water yield in cultivation of cauliflower depends on the chemical composition of the water used in the nutrient solution. The cauliflower production is viable in hydroponics using waters with electrical conductivities of up to 5.88 dS m-1.